Unbreakable Digital Watermarking Technique - Abdulkareem O. Ibadi (QALAAI ZANIST JOURNAL, 2021)
In this research, a new concept of watermarking method is introduced; it is suitable for any type of information file. It doesn’t make any change on the watermarked file. The concept is to store secure watermarking file (SWF) in a reliable third party (RTP). SWF is generated by locating the logo file in the watermarked file. SWF is formatted in special compressed form and can be compressed and encrypted using any suitable application.